5b+15=60

Simple and best practice solution for 5b+15=60 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5b+15=60 equation:


Simplifying
5b + 15 = 60

Reorder the terms:
15 + 5b = 60

Solving
15 + 5b = 60

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '-15' to each side of the equation.
15 + -15 + 5b = 60 + -15

Combine like terms: 15 + -15 = 0
0 + 5b = 60 + -15
5b = 60 + -15

Combine like terms: 60 + -15 = 45
5b = 45

Divide each side by '5'.
b = 9

Simplifying
b = 9

See similar equations:

| (5a^3-4a+2)+(-7a^3-5a+2)= | | m-15=25 | | 4x+1=2x+6 | | 10j=100 | | 4(m+5)+6=7(m+3)-8m | | 65=4b+5 | | 4x-6=10x+10 | | 4x-9=3-(x-2) | | 18k+27= | | 2x-7+3x=11+x+2 | | 4(3c-2)=9c-7 | | 5-3(2d+5)=2 | | 6d+5=11 | | .6666667q-2=.3333333q+7 | | y+25=40 | | (3x+10)+(7x-30)=180 | | 9-8.2= | | 9(2k+3)= | | 5x+4(3x-16)=140 | | -6x+40=-3x-11 | | 0.5x^2*x^2=0 | | 2x+8=4x-128 | | 6x^2-x+13=0 | | 47=w-8 | | 5p-17=2(-2p-7) | | 2[7-6(1-n)]+9n=-20+4[6(n+1)-3n] | | 4(x+6)=35 | | -10x-3(9-x)=4(-2+5)-12 | | 2(x+1)=38 | | 24-5m= | | 2[7-6(1-n)]+8n=-14+3[6(n+1)-3n] | | 0.5x*x=0 |

Equations solver categories